What Obeah Does Do: : Healing, Harm, and the Limits of Religion - Crosson, J. Brent (Journal of Africana religions, 2015)
Obeah, which colonial ordinances defined capaciously as any assumption of supernatural power, was a crime in Trinidad until 2000, and the law continues to make Obeah a punishable offense in most of the anglophone Caribbean. Scholars have noted that contemporary attitudes toward Obeaha hard-to-define termare largely negative, implying spiritual harm. My fieldwork in a region of Trinidad regarded as the island's capital of Obeah, however, revealed polyvalent, context-contingent attitudes toward the term. Using ethnographic examples, I offer alternatives to scholarly approaches that have explained away Obeah's harm as evidence of colonial false consciousness. My interlocutors took shifting, even contradictory stances toward Obeah that depended on tactical contexts of power. By examining attempts to intervene in the justice system through spiritual force, I argue that Obeah is a justice-making technology and that, like all systems of law, the potential for harm is part of its power. In the final part of the paper, I argue that rather than conforming to a definition of religions as mutually exclusive confessional communities rooted in collective avowals of belief, Obeah models a counterdiscourse on social relations that I call altered solidarities, challenging regnant conceptions of religion as the basis for legal recognition in modern states.